2020
DOI: 10.1093/mnras/staa2386
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the planetary dynamics of HD 206893 with ALMA

Abstract: Radial substructure in the form of rings and gaps has been shown to be ubiquitous among protoplanetary discs. This could be the case in exoKuiper belts as well, and evidence for this is emerging. In this paper we present ALMA observations of the debris/planetesimal disc surrounding HD 206893, a system that also hosts two massive companions at 2 and 11 au. Our observations reveal a disc extending from 30 to 180 au, split by a 27 au wide gap centred at 74 au, and no dust surrounding the reddened brown dwarf (BD)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 136 publications
(214 reference statements)
12
67
1
Order By: Relevance
“…In Section 3.4 we show that the brown dwarf is likely responsible for stirring the planetesimals in the debris disk, lending some strength to this scenario. Delorme et al (2017) and Stolker et al (2020) suggested there may be a circumplanetary disk around HD 206893 B (similar to predictions around the red companion G 196-3 B Zakhozhay et al 2017) though recent ALMA observations of the system by Marino et al (2020) showed no dust around the brown dwarf, with a dust upper limit of 2 × 10 −4 M ⊕ .…”
Section: Atmospheric Propertiessupporting
confidence: 60%
See 3 more Smart Citations
“…In Section 3.4 we show that the brown dwarf is likely responsible for stirring the planetesimals in the debris disk, lending some strength to this scenario. Delorme et al (2017) and Stolker et al (2020) suggested there may be a circumplanetary disk around HD 206893 B (similar to predictions around the red companion G 196-3 B Zakhozhay et al 2017) though recent ALMA observations of the system by Marino et al (2020) showed no dust around the brown dwarf, with a dust upper limit of 2 × 10 −4 M ⊕ .…”
Section: Atmospheric Propertiessupporting
confidence: 60%
“…Delorme et al (2017) and Ward-Duong et al (2021) both showed that extinction due to submicron forsterite particles in the brown dwarf's atmosphere could lead to sufficient reddening of its emission spectrum to explain the observations, though they did not take into account the feedback between the submicron particles and the atmosphere. A possible source of these submicron particles is that the brown dwarf may be accreting dust from the debris belt, populating the atmosphere with small, high-altitude grains (Marino et al 2020;Ward-Duong et al 2021). In Section 3.4 we show that the brown dwarf is likely responsible for stirring the planetesimals in the debris disk, lending some strength to this scenario.…”
Section: Atmospheric Propertiesmentioning
confidence: 87%
See 2 more Smart Citations
“…The brightest amongst these discs have been imaged, from scattered light observations in the visible to thermal imaging up to millimetre wavelengths, revealing that most resolved discs display pronounced spatial structures, such as rings, warps, clumps, spirals, etc. (Krivov 2010;Marino et al 2020).…”
Section: Introductionmentioning
confidence: 99%